Efektivitas Penerapan Problem Based Learning Berbantuan Bahan Ajar Inovatif Terhadap Literasi Sains Siswa SMA - Siti Nurhaliza Br Perangin Angin; Sheila Fitriana; Rachmat Rizaldi; Nana Mardiana; Syahwin; Tri Astuti Mardiana (Universitas Garut, 2026)
This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model combined with E-Modules in improving high school students' science literacy in the subject of sound and light waves. The background to this study is the low level of science literacy among Indonesian students according to the PISA report, which ranks Indonesia at the bottom. PBL was chosen because it emphasises real-world problem solving, thereby encouraging active engagement, scientific reasoning, and collaborative skills. E-Modules are used as interactive, flexible, and independent learning-supporting digital teaching materials. This research sample consisted of 60 Grade XI students from Mitra Inalum Private High School, comprising 30 students in the experimental class and 30 students in the control class. The results of the analysis show that the application of PBL assisted by E-Modules has a significant effect on improving science literacy, as evidenced by the Independent Sample T-Test at α = 0.05 with a 2-tailed sig. of 0.000 and N-Gain value of 0.70 for the experimental class and 0.65 for the control class, indicating a higher increase in science literacy in the experimental class. In addition, 84.41% of students responded positively to the use of E-Modules. Thus, the integration of PBL and E-Modules is effective as a 21st-century physics learning strategy.